The effects of stimulus rate and electrode montage on the auditory brainstem response in infants - Dzulkarnain, Ahmad Aidil Arafat; Abdul Hadi, Umi Sarah; Zakaria, Nur 'Azzah (Maney Publishing, 2013)
Purpose